Consumption and hours between the United States and France - Lei Fang; Fang Yang (Federal Reserve Bank of Atlanta, 2021)
We document large differences between the United States and France in allocations of consumption expenditures and time by age. Using a life-cycle model, we quantify to what extent tax and transfer programs and market and home productivity can account for the differences. We find that while labor efficiency by age and home-production productivity are crucial in accounting for the differences in the allocation of time, the consumption tax and social security are more important regarding allocation of expenditures. Adopting the U.S. consumption tax decreases welfare in France, and adopting the U.S. social security system increases welfare in France.
Keywords: E21; E62; J22; O57; H31; 330; consumption expenditure; home production; labor supply; fiscal policy